PENGARUH LATIHAN DEAD LIFT TERHADAP KEKUATAN OTOT TUNGKAI ATLET ANGKAT BESI PRINCE GYM PEKANBARU - Taufiqurrahman, Tengku Fahmi; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is the strength of the leg muscles of the weight lifting athletes at Prince Gym Pekanbaru when doing weight lifting exercises, the researchers still see that when they pull the weights using the muscles of the legs, which makes the force wrong. The purpose of this study was to study the combination of deadlift exercises against leg strength of weightlifting athlete Prince Gym Pekanbaru who controls 6 people. In the investigation, the sampling technique used was total sampling, so the samples in this study were 6 athletes of Weightlifting Prince Gym Pekanbaru. The instruments used to collect data are pre and post test leg dynamometer. The data analysis technique used is the t-test. From the results of the pre-test normality test and the post-test leg dynamometer weightlifting athlete, Prince Gym Pekanbaru obtained a pre-test of 0.1112 and a post-test of 0.1421 with a value of Ltable according with the sample size of 6 people, that is, 0.319. Capable of L_table> L_count or 0.319> 0.1112 and 0.1421 so that it can be resolved with normally distributed data. Based on the results of the t test, t_count = 3,685> t_table = 2,015 was obtained. Weightlifting against muscular leg strength of weightlifting athlete Prince Gym Pekanbaru.Key Words: Dead Lift, Strength of Leg Muscles